Chemoautotrophic Thermodesulfobacteriota as a key genomic potential group in the hypoxic diazotrophic community of the Changjiang (Yangtze River) estuary - Zhang, Mengjia; Zhu, Yuanli; Sun, Zhenhao; Wang, Bin; Chen, Jianfang; Zhou, Feng; Zeng, Jiangning; Li, Meng; Zou, Dayu; Jiang, Zhibing (Frontiers in Microbiology, 2025)
Coastal hypoxia, intensified by global warming and eutrophication, profoundly affects marine nitrogen cycling. However, its impact on diazotrophic communities in large river estuaries remains poorly understood. During an unprecedented hypoxia event (minimum dissolved oxygen at 2.70 μmol L−1) in August 2016 in the Changjiang Estuary, we sampled across a dissolved oxygen (DO) gradient spanning hypoxic and non-hypoxic waters. Using nifH gene amplicon sequencing, metagenomic binning, and multivariate statistical analyses, we found that higher diazotrophic biodiversity was observed in hypoxia zone, with non-cyanobacterial diazotrophs dominating the communities. The phylum Thermodesulfobacteriota (with relative abundance of 58.93% totally) exhibited significant hypoxia-specific enrichment. LEfSe analysis identified Thermodesulfobacteriota as potential hypoxia biomarkers, while network analysis revealed their keystone role, representing 68.6% of highly connected nodes. Environmental drivers, including low DO concentrations (7.50–61.88 μmol L−1 in hypoxic vs. 66.56–255.63 μmol L−1 in non-hypoxic zones), elevated salinity (30.67–34.50), increased dissolved reactive phosphorus (0.39–1.26 μmol L−1), and nitrate depletion (0.30–22.50 μmol L−1), collectively created favorable conditions for the development of the observed diazotrophic community under hypoxia. Metagenomic analysis revealed a hypoxia-driven increase in nifH gene abundance, with nifH-carrying metagenome-assembled genomes affiliated with Thermodesulfobacteriota showing approximately a 4.7-fold higher relative abundance in hypoxic zone compared to non-hypoxic zone. Reconstruction of metabolic pathways from metagenome-assembled genomes (MAGs) further suggested their potential involvement in both nitrogen fixation and carbon–sulfur cycling. Amplicon and metagenomic datasets consistently demonstrated Thermodesulfobacteriota’s predominant in hypoxia. These findings redefine estuarine nitrogen flux models by highlighting hypoxia-driven taxonomic and functional shifts in diazotrophic communities, and provide a foundation for assessing the potential microbial resilience and ecosystem risks in expanding coastal hypoxic zones. Our study underscores the genomic potential of Thermodesulfobacteriota as key players in the nitrogen cycle under hypoxia, a hypothesis that warrants future validation through direct activity measurements.